Parametric analysis of the transmission dynamics during indigenous aggregated outbreaks caused by five SARS-CoV-2 strains in Nanjing, China - Ma, Tao; Chen, Cong; Wang, Junjun; Wang, Hengxue; Zhao, Yueyuan; Zhu, Yuanzhao; Yan, Zikang; Ding, Songning; Ding, Jie (Frontiers in Public Health, 2024)
Background SARS-CoV-2 strains have been of great concern due to their high infectivity and antibody evasion.Methods In this study, data were collected on indigenous aggregated outbreaks in Nanjing from January 2020 to December 2022, caused by five strains including the original strain, the Delta variant, and the Omicron variant (BA.2, BA.5.2, and BF.7). The basic epidemiological characteristics of infected individuals were described and then parametric analysis of transmission dynamics was performed, including the calculation of incubation period, serial interval (SI), the basic reproductive number (R0), and the household secondary attack rate (HSAR). Finally, we compared the trends of transmission dynamic parameters of different strains.The incubation period for the original strain, the Delta variant, Omicron BA.2, Omicron BA.5.2, and Omicron BF.7 were 6d (95%CI: 3.5-7.5d), 5d (95%CI: 4.0-6.0d), 3d (95%CI: 3.0-4.0d), 3d (95%CI: 3.0-3.0d), and 2d (95%CI: 2.0-3.0d), respectively; Also, the SI of the five strains were 5.69d, 4.79d, 2.7d, 2.12d, and 2.43d, respectively. Notably, the incubation period and SI of the five had both a progressive shortening trend (P<0.001);